The Relationship Between Physical Activity and the Risk of Diabetes Mellitus in High School Adolescents in Malang City - Susi Milwati; Dyah Widodo; Lucia Retnowati (Jurnal Keperawatan Terapan, 2021)
Diabetes mellitus is a disease caused by a hormonal disorder that affects insulin 5.7% of the total population of Indonesia, including teenagers. Is a big challenge for the health sector to do the step in anticipation of the complexity of health problems caused by diabetes mellitus in Indonesia. This study aims to analyze the relationship of physical activity with the risk of diabetes mellitus in adolescent high school in the city of Malang. This research is correlational research design, sampled in this study is partly a teenage high school class in Malang, city area drawn at random sampling with a large sample of 375 respondents. Research conducted at the high school SMU Negeri 6 and SMU Negeri 9 in the city of Malang, in May-August 2021. Data collection techniques using questionnaires. Data analysis is descriptive and analytic Spearman Rho correlation with alpha 0.05 using computer. The results showed that there is no relationship of physical activity with the risk of diabetes mellitus in adolescent high school in Malang. Recommended for teens to pay attention to healthy activity, so avoid the risk of diabetes mellitus